The Contribution of the North Sumatra Regional Broadcasting Commission (KPID) in Supervising the Broadcast of the Governor's Election Campaign North Sumatra in 2024 - Ahmad Kurniawan Harahap; Mardian Idris Harahap; Aminuddin; Anggia Ramadhan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Law No. 32 of 2002 gave birth to a new chapter in the world of broadcasting in Indonesia, through which it is regulated regarding all matters related to the world of broadcasting. Including the establishment of all independent institutions that regulate and control national broadcasting. The institution was named the North Sumatra Indonesian Broadcasting Commission. This research aims to find out the contribution of the North Sumatra KPID in supervising campaign broadcasts in the 2024 North Sumatra Governor Election. Then to analyze what strategy is used by the North Sumatra KPID in supervising campaign broadcasts in the 2024 North Sumatra Governor Election. The research used is descriptive. Data collection was carried out through in-depth interviews with the Commissioner of the Indonesian Broadcasting Commission of North Sumatra. The results of the study show that the Indonesian Broadcasting Commission of North Sumatra has made a very positive contribution in carrying out the supervision of campaign broadcasts. This is strengthened by the work carried out by KPI D North Sumatra which was positively welcomed by the community. The Indonesian Broadcasting Commission of North Sumatra also took strategic steps in supervising campaign broadcasts in the Governor and Deputy Governor Elections of North Sumatra